The Intersection of Tradition and Choice: A Study of Spouse Selection in Pakistan’s Nomadic Tribe - Qadeer, Abdul; Sharif , Abida; Sadaf, Fouzia (Pakistan Journal of Humanities and Social Sciences, 2022)
In an intricate examination of spouse selection within the Bagri tribe, a nomadic community in Pakistan, this study dissects the multi-tiered, socio-cultural dynamics that govern matrimonial decisions. Drawing upon qualitative research, comprising in-depth interviews with 15 respondents from the Bagri tribe in Balochistan and Sindh provinces, the study illuminates the tripartite influence of spouses, parents, and the tribal council known as "Panchayat." The findings unearth a hierarchy of authority, with spouses wielding minimal influence, parents exerting substantial control, and the Panchayat often having the final say. Contrasting the male and female roles, the study observes a gender-based disparity where men possess a slightly greater agency in spouse selection. Moreover, the process is steeped in culturally rich rituals and symbolic gestures, such as "Shagun" and engagement ceremonies, reflecting the tribe's social ethos. The paper situates these practices within theoretical frameworks such as Social Conflict Theory, Family System Theory, and Social Exchange Theory, offering a nuanced understanding of how decisions regarding marital unions are negotiated, ritualized, and enacted. Comparing these patterns with other cultural contexts, the study contributes an enriched perspective to the existing body of knowledge on spouse selection, emphasizing the complex interplay between individual choice, familial dictates, community norms, and traditional customs.